Ungdomars samtal kring risker i trafiken: Relationen mellan riskförståelse och platsanknytning (Sociologisk Forskning, 2009)
Young people talking about risk in traffic milieus: the relationship between sensemaking of risk and place attachment This explorative study investigates the relationship between sensemaking of risk and place attachment among young people. Traffic safety behaviours are focused. Eight focus group interviews have been done, with a total number of 36 interviewees in the age of 16–20 years. Half of the groups where made in Greater Stockholm, and half in the county of Jämtland. Four aspects of place attachment where explored. The results show that particularly socialbelonging is of a great matter within young people’s sensemaking of risk in this context. The study implies the importance of further studies of sensemaking of risk in general, and of young people’s sensemaking of risk in traffic milieus in particular.